2012
DOI: 10.2136/sssaj2011.0443
|View full text |Cite
|
Sign up to set email alerts
|

Near Infrared Reflectance Spectroscopy Prediction of Soil Nitrogen Supply in Humid Temperate Regions of Canada

Abstract: Near infrared reflectance spectroscopy (NIRS) holds promise for rapid assessment of soil total N and organic C contents, but its ability to predict soil N supply in soils with contrasting physio-chemical properties needs to be evaluated. The objectives of this study were to: (i) evaluate NIRS predictions of measured soil parameters (total N, organic C, and C/N ratio) and as an indirect indicator of soil N supply, namely corn (Zea mays L.) N uptake and (ii) assess the effect of sample set heterogeneity on NIRS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Previous studies at field scale in Canada reported excellent estimation by NIR-PLSr for SOC (R 2 = 0.86-0.98; RPD = 2.9-3.6) and TN (R 2 = 0.83-0.93; RPD = 3.4-4.8) (Nduwamungu et al 2009), or reliable estimation for SOC (R 2 = 0.875; RPD = 2.16) and poor estimation for soil organic N (R 2 = 0.326; RPD = 1.22) (Martin et al 2002). Reliable estimation by NIR-PLSr for SOC (R 2 = 0.86; RPD = 2.65) and TN (R 2 = 0.85; RPD = 2.56) was found for soils from the eastern Canada (St. Luce et al 2012), and excellent estimation by VNIR-PLSr for SOC (R 2 = 0.92; RPD = 3.70) and TN (R 2 = 0.93; RPD = 3.83) were found for the soils from the western Canada (St. Luce et al 2014). A previous study carried out at the same site (Woodslee), including the 50 samples used in this study and 245 more samples from other field trials at the same experimental farm (CV for SOC = 60%; CV for TN = 40%; ranging 3.4-36.5 g C kg −1 , 0.6-2.8 g N kg −1 ), provided excellent predictions for SOC and TN (R 2 = 0.96-0.99 for MIR and R 2 = 0.95-0.97 for NIR, the RPD values > 4) (Xie et al 2011).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Previous studies at field scale in Canada reported excellent estimation by NIR-PLSr for SOC (R 2 = 0.86-0.98; RPD = 2.9-3.6) and TN (R 2 = 0.83-0.93; RPD = 3.4-4.8) (Nduwamungu et al 2009), or reliable estimation for SOC (R 2 = 0.875; RPD = 2.16) and poor estimation for soil organic N (R 2 = 0.326; RPD = 1.22) (Martin et al 2002). Reliable estimation by NIR-PLSr for SOC (R 2 = 0.86; RPD = 2.65) and TN (R 2 = 0.85; RPD = 2.56) was found for soils from the eastern Canada (St. Luce et al 2012), and excellent estimation by VNIR-PLSr for SOC (R 2 = 0.92; RPD = 3.70) and TN (R 2 = 0.93; RPD = 3.83) were found for the soils from the western Canada (St. Luce et al 2014). A previous study carried out at the same site (Woodslee), including the 50 samples used in this study and 245 more samples from other field trials at the same experimental farm (CV for SOC = 60%; CV for TN = 40%; ranging 3.4-36.5 g C kg −1 , 0.6-2.8 g N kg −1 ), provided excellent predictions for SOC and TN (R 2 = 0.96-0.99 for MIR and R 2 = 0.95-0.97 for NIR, the RPD values > 4) (Xie et al 2011).…”
Section: Discussionmentioning
confidence: 96%
“…Luce et al 2014) at different scales (local, regional, national, or global). In Canada, MIR and NIR spectroscopies have been successfully used to estimate C and N in bulk soils (Martin et al 2002;Nduwamungu et al 2009;Xie et al 2011;St. Luce et al 2012;St.…”
Section: Introductionmentioning
confidence: 99%
“…The modified partial least squares regression method (PLSR) of the WinlSI III software was used to develop calibration equations for the soil and crop properties. To maximize the probability of developing a robust calibration equation for each property, a maximal number of soil samples, corresponding to 80% of each soil sample set, were randomly selected by the software to be used for the calibration set, and the remainder samples were used for the validation set (Ludwig et al, 2002;Brunet et al, 2007;St. Luce et al, 2012).…”
Section: Pretreatment Calibration and Cross-validationmentioning
confidence: 99%
“…Predicting crop P-uptake and P-budget from soil spectra would eliminate the need to establish relationships between soil test P and crop response to P fertilization. Börjesson et al (1999), Terhoeven-Urselmans et al (2008), and more recently St. Luce et al (2012) link NIRS soil spectra to winter cereal N-uptake and report good predictions (i?^^ > 0.70), but to our knowledge, the prediction of crop P-uptake and annual P-budget by NIRS has not been documented.…”
mentioning
confidence: 99%
“…A prototype mid-IR spectrophotometer is a further addition to the ISE which will allow for the integration of sensors based on different measurement principles [ 44 , 45 ]. However, applicability of this instrument to predict SOC and texture in comparison with the earlier mentioned P4000 unit needs to be assessed on many diverse soil samples [ 46 ].…”
Section: Introductionmentioning
confidence: 99%